Students' Interest in Occupational Health and Safety (K3) Subject and its Correlation with Discipline in Using Personal Protective Equipment During Welding Practices Among Eleventh Grade Students of the Welding Engineering Program at SMK Negeri 2 Bitung - I.Parsaoran Tamba (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Occupational Safety and Health (K3) education is essential in vocational high schools (SMK), particularly for welding engineering students, as it equips them with the knowledge to prevent workplace accidents. Welding practices expose students to physical and chemical hazards, which can lead to injuries such as electric shocks, respiratory issues, and skin burns. The use of Personal Protective Equipment (PPE) is critical in mitigating these risks. This study aims to examine the relationship between students' interest in K3 subject matter and their discipline in using PPE during welding practice. A survey method was employed, with data collected from 22 Grade XI welding students at SMK Negeri 2 Bitung. Parametric statistical analysis, including correlation and linear regression, was used to analyze the data. Results indicate a high level of student interest in K3 material () and a disciplined approach to PPE usage (). A very strong positive correlation () was found between interest and discipline, with interest accounting for 71% () of the variance in disciplined PPE use, as modeled by the regression equation . The study concludes that fostering student interest in K3 education significantly enhances disciplined PPE adherence, thereby promoting safer welding practices